APLIKASI PUPUK KOMPOS DAN FREKUENSI PEMUPUKAN NPK DALAM MENINGKATKAN PRODUKSI BAWANG MERAH (Allium ascalonicum L) PADA TANAH GAMBUT - Selvia Sutriana; M. Nur (DINAMIKA PERTANIAN, 2018)
ABSTRACT Peatlands is a very specific ecosystem with conditions that are always flooded, fragile, relatively infertile, able to absorb more water, and bad aeration. Riau has the largest peat land, which is 64% of the total peatlands area in Sumatra, but the development of shallot has not been intensively cultivated. So it must be dealt with seriously. The use of compost fertilizer and the frequency of NPK apply can improve the nature of these peatlands and increase crop production. The aim of study was to determine the interaction effect and the main application of compost and the frequency of NPK apply to increasing shallot production on peat soil. Research conducted at the Faculty of Agriculture Experimental Farm, Riau Islamic University during 6 month, i.e. form March - August 2018. Factorial Completely Randomized Research design, the first factor was 10, 20 and 30 tons/ha of corn compost, the second factor was NPK 16:16:16 fertilization frequency 1 and 2 fertilizing doses of 150, 300 and 450 kg/ha. Parameters observed were peat analysis, tuber number, tuber diameter, wet tuber weight per clump, dry tuber weight per clump and percentage of tuber shrinkage. The results showed that the interaction and main effects were significant for all observed parameters with the best treatment of compost is 30 tons/ha and 2 times the fertilizer dose of 150 kg/ha per application (300 kg/ha). Keywords: Shallot, Frequency, Compost, Fertilization, NPK, Production